2016
DOI: 10.4103/0973-1296.177912
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel human epidermal growth factor Receptor-2 inhibitors by structure-based virtual screening

Abstract: Background:Human epidermal growth factor receptor-2 (HER2) is a trans-membrane receptor like protein, and aberrant signaling of HER2 is implicated in many human cancers, such as ovarian cancer, gastric cancer, and prostate cancer, most notably breast cancer. Moreover, it has been in the spotlight in the recent years as a promising new target for therapy of breast cancer.Objective:Since virtual screening has become an integral part of the drug discovery process, it is of great significant to identify novel HER2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In senescence-accelerated mice-prone 8 (SAMP8), a model characterized by the early onset of learning and memory deficits along with overproduction of soluble amyloid peptide in the brain, the chronic treatment with green tea catechins (GTC) (0.05% and 0.1% in drinking water for 6 months) restored the reduction of mBDNF levels in the hippocampus and prevented the learning impairment of SAMP8 mice [ 79 ]. Finally, 4 months of EC administration (50 mg/kg daily in drinking water) normalized the low levels of BDNF protein in the hippocampus of 8-month-old APP/PS1 mice, without affecting escape latency in MWM [ 80 ].…”
Section: Green Tea ( Camellia Sinensis (L) Kunmentioning
confidence: 99%
“…In senescence-accelerated mice-prone 8 (SAMP8), a model characterized by the early onset of learning and memory deficits along with overproduction of soluble amyloid peptide in the brain, the chronic treatment with green tea catechins (GTC) (0.05% and 0.1% in drinking water for 6 months) restored the reduction of mBDNF levels in the hippocampus and prevented the learning impairment of SAMP8 mice [ 79 ]. Finally, 4 months of EC administration (50 mg/kg daily in drinking water) normalized the low levels of BDNF protein in the hippocampus of 8-month-old APP/PS1 mice, without affecting escape latency in MWM [ 80 ].…”
Section: Green Tea ( Camellia Sinensis (L) Kunmentioning
confidence: 99%
“…However, in silico studies on HER2 require immediate attention because, so far, no receptor crystals have been reported that bind to compounds that have been used in therapy, such as lapatinib. Currently, the most widely used crystals for the development of HER2 inhibitors are those that bind to experimental drugs, such as 2-{2-[4-({5-chloro-6-[3-(trifluoromethyl)phenoxy]pyridin-3-yl}amino)-5hpyrrolo[3,2-D]pyrimidin-5-yl]ethoxy}ethanol in PDB 3PP0 and TAK-285 in PDB 3RCD, as reported by Shi et al [55] and Yousuf et al [56]. Furthermore, in studies conducted by Li et al [53] and Yang et al [54], lapatinib was used as a reference ligand for these receptors.…”
Section: Discussionmentioning
confidence: 87%
“…For example, Foretinib, a multi-target kinases inhibitor against both c-Met and VEGFR2, is currently under phase II trials [39]. Cabozantinib, an orally bioavailable tyrosine kinase inhibitor which targeting a number of tyrosine kinases, including RET, KIT and AXL, c-Met, etc., has been approved for the treatment of patients with progressive, metastatic medullary thyroid carcinoma [40,41]. However, novel inhibitors are still urgently waited for anti c-Met therapy in context of breast cancer.…”
Section: Discussionmentioning
confidence: 99%